Analysis of knowledge about arboviruses and preventive measures among the population living in Belém and Ananindeua, Pará (Research, Society and Development, 2025)
Sanitation is essential for improving quality of life and for the sustainable development of populations, with access to safe drinking water and adequate sewage systems being fundamental to people’s health and well-being. Climate change has intensified health problems, including an increase in mosquito-borne diseases such as dengue, Zika, chikungunya, yellow fever, malaria, and leishmaniasis, as well as worsening respiratory and cardiovascular conditions related to extreme heat and pollution. This scenario is particularly relevant in the Amazon, a region characterized by a hot and humid climate, fragile soils, and communities with diverse ways of life, requiring integrated solutions in sanitation, mobility, urbanization, and health promotion. The study aimed to investigate the sociodemographic profile of 960 participants, as well as the population’s habits and prevention strategies, with a focus on dengue.The results revealed that, despite high levels of knowledge about the disease and its symptoms, gaps remain in the adoption of preventive measures. Social vulnerability, deficiencies in basic sanitation, and environmental factors contribute to the persistence of mosquito breeding sites, highlighting the need for health education and community engagement. It is concluded that educational actions, preventive campaigns, and social mobilization strategies are fundamental to reducing the incidence of arboviruses, strengthening community protagonism, and promoting practices that protect collective health in the Metropolitan Region of Belém and Ananindeua.